2020
DOI: 10.1016/j.jadohealth.2020.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Rebound of Severe Alcoholic Intoxications in Adolescents and Young Adults After COVID-19 Lockdown

Abstract: Purpose The coronavirus lockdown in Italy ended, but the postlockdown phase may be even more challenging than the outbreak itself if the impact on mental health is considered. To date, little evidence is available about the effect of lockdown release in terms of adolescent health from the perspective of an emergency department (ED). Methods We reviewed data on ED arrivals of adolescents and young adults (aged 13–24 years) in the weeks immediately before and after the It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
52
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 8 publications
(9 reference statements)
6
52
0
4
Order By: Relevance
“…13 studies reported short-term consequences of lockdown with psychiatric symptoms, sleep disturbance, economic aftereffects, behavioural changes, and social repercussions described ( Figure 2 ) [ 15 , 19 - 21 , 28 - 30 , 35 , 44 , 50 - 52 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 studies reported short-term consequences of lockdown with psychiatric symptoms, sleep disturbance, economic aftereffects, behavioural changes, and social repercussions described ( Figure 2 ) [ 15 , 19 - 21 , 28 - 30 , 35 , 44 , 50 - 52 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Psychiatric symptoms, stress, stigmatisation, sleep disturbance, and increased emergency department attendances with alcohol intoxication were identified following COVID-19 lockdown measures [ 19 - 21 , 29 , 30 , 50 - 52 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports have linked exposure to catastrophic societal events and natural disasters to increased alcohol use ( Morita et al., 2015 ; Locke et al., 2020 ). Indeed, many reports have now demonstrated that alcohol use has increased significantly since the beginning of the COVID-19 pandemic ( Ahmed et al., 2020 ; Clay et al., 2020 ; Dumas et al., 2020 ; Grigoletto et al., 2020 ; Kim et al., 2020 ; Lechner et al., 2020 ; Neill et al., 2020 ; Pollard et al., 2020 ; Stanton et al., 2020 ; Tran et al., 2020 ; Vanderbruggen et al., 2020 ; Wardell et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study examining changes in wastewater reported ‘decreased’ alcohol consumption after self-isolation measures were enforced in the district ( Bade et al., 2020 ), whereas two other longitudinal studies reported results in-line with ‘increases’ observed in cross-section. A national cohort study in the USA reported increases in alcohol consumption from assessments completed in April 2019 to April 2020 ( Pollard et al., 2020 ), and a second study reported increased emergency room visits due to alcohol intoxication documented via chart review prior to and during the pandemic ( Grigoletto et al., 2020 ). In addition to examining changes in alcohol use several studies have examined factors associated with those changes including alcohol-related coping motives ( Wardell et al., 2020 ), inhibitory control ( Clay et al., 2020 ), symptoms of anxiety or depression ( Dumas et al., 2020 ; Lechner et al., 2020 ; Neill et al., 2020 ; Rodriguez et al., 2020 ; Stanton et al., 2020 ; Tran et al., 2020 ; Wardell et al., 2020 ), social connectedness ( Lechner et al., 2020 ; Wardell et al., 2020 ) and loss of job or income ( Neill et al., 2020 ; Vanderbruggen et al., 2020 ; Wardell et al., 2020 ), all documented in cross-sectional analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation